An Analysis of Geometrical and Failure Characteristics of Laser Micro-Welded SS304 and DSS2205 - R. M. Mithun; M. M. Quazi; M. Nasir Bashir; M. Ishak; M. H. Aiman (Journal of ICT, Design, Engineering and Technological Science, 2021)
Laser micro-welding is being widely used in many industries because of its speed and precision. This study's Stainless Steel (SS304) and Duplex Stainless Steel (DSS 2205) possess good ductility and strength. However, laser micro-welding is a challenge for joining dissimilar materials. Pulse wave mode micro-welding was employed in this study. The parameters that were varied throughout the study were the peak power and hatching distance. With that being so, the other parameters such as frequency, pulse width, mark loop and welding speed were kept constant. After preliminary tests were carried out, a range of parameters was obtained by knowing the threshold value to obtain a proper joint. The welded specimens were analyzed by conducting weld geometrical properties analysis, failure analysis with the aid of image analysis software (Image J), and surface color examination. The strongest tensile strength value obtained was 13.56 MPa with a weld width of 0.611mm, whereas the least tensile strength value was 0.8 MPa with a weld width of 0.577mm. A percentage difference of 177.015% between the highest and lowest tensile stress value was observed. The highest distortion lies with specimen I (power 95%, hatching distance 0.001mm) with an angular deviation of 5.013◦ on the left side and 4.086◦ on the right concerning the horizontal place. It was concluded that too high power caused distortion, thereby resulting in a poor joint.